Exoskeleton Training and Trans-Spinal Stimulation for Physical Activity Enhancement After Spinal Cord Injury (EXTra-SCI): An Exploratory Study - Sutor, Tommy W.; Ghatas, Mina P.; Goetz, Lance L.; Lavis, Timothy D.; Gorgey, Ashraf S. (Frontiers in Rehabilitation Sciences, 2022)
After spinal cord injury (SCI) physical activity levels decrease drastically, leading to numerous secondary health complications. Exoskeleton-assisted walking (EAW) may be one way to improve physical activity for adults with SCI and potentially alleviate secondary health complications. The effects of EAW may be limited, however, since exoskeletons induce passive movement for users who cannot volitionally contribute to walking. Trans-spinal stimulation (TSS) has shown the potential to enable those with even the most severe SCI to actively contribute to movements during EAW. To explore the effects of EAW training on improving secondary health complications in persons with SCI, participants with chronic (n = 8) were enrolled in an EAW program 2–3 times per week for 12 weeks. Anthropometrics (seated and supine waist and abdominal circumferences (WC and AC), body composition assessment (dual exposure x-ray absorptiometry-derived body fat percent, lean mass and total mass for the total body, legs, and trunk), and peak oxygen consumption (VO2 during a 6-minute walk test [6MWT]) were assessed before and after 12 weeks of EAW training. A subset of participants (n = 3) completed EAW training with concurrent TSS, and neuromuscular activity of locomotor muscles was assessed during a 10-m walk test (10MWT) with and without TSS following 12 weeks of EAW training. Upon completion of 12 weeks of training, reductions from baseline (BL) were found in seated WC (−2.2%, P = 0.036), seated AC (−2.9%, P = 0.05), and supine AC (−3.9%, P = 0.017). Percent fat was also reduced from BL for the total body (−1.4%, P = 0.018), leg (−1.3%, P = 0.018), and trunk (−2%, P = 0.036) regions. No effects were found for peak VO2. The addition of TSS for three individuals yielded individualized responses but generally increased knee extensor activity during EAW. Two of three participants who received TSS were also able to initiate more steps without additional assistance from the exoskeleton during a 10MWT. In summary, 12 weeks of EAW training significantly attenuated markers of obesity relevant to cardiometabolic health in eight men with chronic SCI. Changes in VO2 and neuromuscular activity with vs. without TSS were highly individualized and yielded no overall group effects.